A new efficient method for solving quadratic Riccati differential equation - Batiha, Belal (International Journal of Applied Mathematical Research, 2015)
A new efficient method called the multistage variational iteration method (MVIM) is applied to the solution of quadratic Riccati differential equations. A comparison between MVIM solution with classical variational iteration method (VIM) and exact solution has been made and show that the MVIM is a powerful method to the solution of nonlinear differential equations.